(untitled) (International Association of Biologicals and Computational Digest, 2022)
Boerhaavia diffusa L. belongs to the family Nyctaginaceae commonly known as “Punarnava” is one of the important plants of Ayurveda, Charaka Samhita and Sushruta Samhita. The plant has immense benefits as a Rasayana- in Rejuvenation benefits. Boerhaavia diffusa L.roots are a very good source of Antioxidants and a natural drug which has innumerable benefits. Hence, the present study was undertaken to identify the functional groups present within the roots. The FT-IR studies showed 12 peaks which confirmed the presence of essential phytochemicals in the crude powdered plant roots.